CAMPUR KODE KATA BAHASA JAWA DALAM PEMAKAIAN BAHASA INDONESIA TULIS SISWA KELAS III MI MIFTAHUL HUDA LAMPUNG TIMUR - Nurida Setyawati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2021)
Bilingualism is a global phenomenon. The language contact that is mastered triggers the mutual influence that occurs in bilinguals. Bilingulisme includes code mixing. Code mixing is the use of two languages ​​at the same time. Code mixing greatly affects the written Indonesian for grade III students of MI Miftahul Huda, East Lampung. The habit of using mixed languages ​​is what causes code mixing in their written Indonesian. The tendency to use the first language (mother) in Javanese greatly affects their written Indonesian.